2015
DOI: 10.1007/s13277-015-3813-4
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β signaling pathway cross-talking with ERα signaling pathway on regulating the growth of uterine leiomyoma activated by phenolic environmental estrogens in vitro

Abstract: The aim of this paper is to study the participation of transforming growth factor-β (TGF-β) signaling pathway in mediating the growth of human uterine leiomyoma (UL) activated by phenolic environmental estrogens (EEs), via the interaction between TGF-β and ER signaling pathways. The UL cells were prepared by primary culture and subculture methods. To validate the role of TGF-β3 (5 ng/ml) for the viability of human uterine leiomyoma cells, CCK-8 assay was performed in each of five treatment groups including E2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…UF cells exhibit excessive sensitivity to estrogens as compared to normal muscle [ 36 , 39 , 80 , 81 ]. The estrogen receptor α signaling pathway has an influence on the TGF-β signaling pathway under the effect of estrogen and other similar molecules [ 82 ]. Studies in UF cell colonies showed that the proliferative potential can be acquired by tumor tissue through estrogen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…UF cells exhibit excessive sensitivity to estrogens as compared to normal muscle [ 36 , 39 , 80 , 81 ]. The estrogen receptor α signaling pathway has an influence on the TGF-β signaling pathway under the effect of estrogen and other similar molecules [ 82 ]. Studies in UF cell colonies showed that the proliferative potential can be acquired by tumor tissue through estrogen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…96 Interestingly, TGF-β expression in the uterus is sensitive to sex steroid hormones and acts downstream of environmental estrogen signaling, a prominent risk factor for UL development. 97,98 TGF-β3 expression levels fluctuate during each phase of the menstrual cycle, peaking at the secretory phase, suggesting regulation by progesterone and estrogen. 94 EGF, PDGF, and VEGF-A levels have been found at significantly higher levels in UL tissue compared with myometrial tissue, although the receptor for EGF (EGFR) is expressed at similar levels between the tissues.…”
Section: Ras/raf/mek/erk Pathwaymentioning
confidence: 99%
“…The proliferation of leiomyoma cells together with excessive deposition of extracellular matrix (ECM) is the crucial pathological process. These two mechanisms are tightly regulated by a complex network of interconnected pathways, including pathways of steroids, growth factors, TGF-β/Smad, Wnt/β-catenin, retinoic acid, vitamin D, and PPARγ (1,2,4). Interestingly, aberrant signal transduction pathways in UL patients are not only intracellular, but also extracellular and intercellular pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, aberrant signal transduction pathways in UL patients are not only intracellular, but also extracellular and intercellular pathways. Furthermore, partly due to the poor understanding of the underlying pathobiology, there is no effective medical treatment currently available (1,4,5). Major therapy strategies are based on the inhibition of estrogen or progesterone, but UL tends to regrow once treatment is stopped.…”
Section: Introductionmentioning
confidence: 99%